RESULTS OF STUDIES ON THE DIAGNOSIS OF BOVINE BRUCELLOSIS USING THE ELISA TEST - Kokilov B.R; Ruzimurodov M.A; Ulug’muradov A.D; Baxriddinov D.I (Western European Studies, 2025)
In order to determine the immune background level against bovine brucellosis, studies were conducted on blood samples taken from 65 cattle in two farms, “Olimjon xazinasi” and “Otajon-ota,” located in Buloqboshi district of Andijan region. When the blood samples were examined using the ELISA test to assess the immune background level, positive results were recorded in 54 cattle (83%) and negative results in 17%.
Keywords: brucellosis; immune background; reaction